Fenomena Digital Burnout dan Krisis Sosial-Emosional di Kalangan Peserta Didik: Peran Konselor dalam Menumbuhkan Keseimbangan Digital - Ziqki Rifki Khadafi; Della Pelita; Tio Gunawan (Sekolah Tinggi Agama Islam As-Sunnah, 2025)
The phenomenon of digital burnout has emerged as a critical challenge in modern education, where students increasingly depend on digital technology for learning and social interaction. Excessive reliance on social media, online games, and other digital activities causes mental fatigue, decreased empathy, and emotional dysregulation. This condition contributes to the decline of students’ social-emotional capacities, leading to reduced face-to-face communication, increased social isolation, and symptoms of stress, anxiety, and depression. This conceptual paper aims to analyze the relationship between digital burnout and social-emotional crises among students, while exploring the counselor’s role in fostering digital balance through developmental psychology and Islamic guidance counseling approaches. Through literature review and theoretical analysis, this study finds that counselors play not only curative but also preventive and educational roles by integrating Islamic spiritual values, digital literacy, and emotional regulation training. Counselors are vital in guiding students toward wise and proportional technology use, thereby achieving digital balance in both academic and social life